2020
DOI: 10.2516/ogst/2020010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of water composition and salinity effect on the oil recovery in carbonate reservoirs

Abstract: Water injection has been known as a conventional approach employed for years in order to achieve higher oil recovery from oil reservoirs. Since the last decade many researchers conducted on the water injection assessment suggested that low salinity water flooding can be an effective flooding mechanism and it can be used as an enhanced oil recovery method. Several examinations were conducted to identify governing mechanisms entailed in oil extraction and the effect of salinity and different types of ionic conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…As a result of this sedimentation, the permeability of these pathways is reduced, and the brine is directed to the intact pathways, resulting in increased sweep efficiency and ultimate oil recovery (Abhishek et al 2018;Chen et al 2021;Mahboubi Fouladi et al 2021;Mardashov et al 2021). Zaheri et al (2020) reported that the type and concentration of the ions in the brine play a vital role in the wettability changes and the ultimate oil recovery. Based on the experimental study, Su et al (2018) observed that the maximum change in wettability is observed at the optimal salt concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this sedimentation, the permeability of these pathways is reduced, and the brine is directed to the intact pathways, resulting in increased sweep efficiency and ultimate oil recovery (Abhishek et al 2018;Chen et al 2021;Mahboubi Fouladi et al 2021;Mardashov et al 2021). Zaheri et al (2020) reported that the type and concentration of the ions in the brine play a vital role in the wettability changes and the ultimate oil recovery. Based on the experimental study, Su et al (2018) observed that the maximum change in wettability is observed at the optimal salt concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the Wettability Alteration (WA) to more water-wet conditions is a crucial parameter to decrease the residual oil saturation (Hirasaki et al, 2004;Saikia et al, 2018;Seethepalli et al, 2004;Webb et al, 2004). Zaheri et al (2020) perform coreflooding analysis with carbonates using LSWI. They observed a relation between higher calcium content in formation water and a more oil-wet condition.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Lashkarbolooki et al (2017) found that NaCl and KCl exhibit different behavior in changing wettability, such that contact angle decreases by increasing KCl concentration or reducing NaCl concentration. Moreover, Zaheri et al (2020) reported that the concentration of CaCl 2 in formation water (FW) can play an important role in wettability alteration.…”
Section: Introductionmentioning
confidence: 99%